Pengembangan Karakter Disiplin Siswa Melalui Rutinitas Religius Pembacaan Ratibul Haddad di MI Al Falah Kanigoro Pagelaran Malang - Suhartini Suhartini; Nihayatin Nikmah; M. Husni Mahrus; Sita Acetylena (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2026)
This study aims to describe the development of students' disciplined character through the religious routine of reciting Ratibul Haddad at MI Al Falah Kanigoro, Pagelaran, Malang. The background of this research is based on the importance of forming disciplined character as a part of Islamic character education integrated into religious activities in elementary schools. The research method used is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The results indicate that the routine recitation of Ratibul Haddad, conducted every morning before classes, is able to foster disciplinary values in students, such as arriving on time, maintaining order, and adhering to school regulations. Furthermore, this activity fosters spiritual awareness and a sense of togetherness among students, while strengthening the religious culture within the school environment. Thus, the religious routine of reciting Ratibul Haddad is proven to be an effective strategy for spiritual-based discipline character building at MI Al Falah Kanigoro, Pagelaran, Malang.